المعالم الأساسیة لاختصاصی المعلومات فی ضوء إدارة المعرفة - د. لطیفة على الکمیشى (المجلة الدولية لعلوم المكتبات والمعلومات)
The term knowledge management of modern terms that are currently widely usedin various parts of the world, which aims to share knowledge, whether thisknowledge implicit or explicit.As a result of the tremendous revolution in information technology has becomeso difficult for the individual to know everything Mantgth Alqrihh humanity in hisfield. In order to cope with this overwhelming revolution of information andimprove the performance of the application of knowledge management is one ofthe means by which organizations can seek refuge in the grounds that knowledgemanagement is in the contemporary world of the most important modern ideaswhich make an effective contribution to the success of businesses andinstitutions.I have appeared several new concepts imposed on us as a result of theemergence of modern technologies such as the concept of data, information andknowledge, has been linked to the researchers between knowledge managementand knowledge management and library science as a result of the vast amount ofinformation became necessary to develop a strategy for how to manage theinformation and then the back of the so-called knowledge management.Knowledge management is also a great opportunity for libraries to raise thequality of services offered by the beneficiaries. Due to the adoption of knowledgemanagement on modern developments in information and communicationtechnology, the libraries and information centers will face serious changesregarding the specifications of its employees and their qualifications and how toacquire the skills and competencies related to the management of knowledgeand modern methods of organizing accessed via networks.